An Extra-curricular activities extension in public elementary schools - Martin, Matronillo Del Mundo; Tugguin, Frazel May Bonesto (Management Research Journal, 2020)
The main purpose of this study is to determine the extent of implementation and level of contribution of the extra–curricular activities in the public elementary schools. Descriptive research was utilized in this study. There were 7 school heads and 64 selected teachers as respondents using total enumeration technique. Information was obtained from the respondents through the use of questionnaires. Quantitative data collected by using a questionnaire were analyzed by the use of descriptive statistics and presented through percentages, means, and frequencies. Findings show that there is an over- all high implementation of the extra-curricular activities in the public elementary school of Aguinaldo District 2. Moreover, pupils have active participation of the different activities through the leadership of the school administrators and teachers. Likewise, the school heads and teachers treat extracurricular activities with similar passion with the curricular activities but with careful discretion in not disrupting regular class schedule. The study also shows that extra-curricular activities can provide better environment for the development of school especially on the nurturing of the pupils. Pupils of the public elementary schools in Aguinaldo District 2 have been actively competing in the different extra-curricular activities which made each school able receive awards in different levels. The success of the school performances requires careful management and good organization. Therefore, support, cooperation and motivation from school administrators, parents and students should necessary in order to maintain excellence achievement and good school performances.